2000
DOI: 10.1128/cdli.7.5.845-849.2000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Phylogenetic Analysis of TT Virus DNA in Western India

Abstract: In western India, TT virus (TTV) DNA positivity varied from 6.7% (5 of 75) in chronic hepatitis patients to 24.4% (10 of 41) in hemophiliacs; 7.4% (4 of 54) of voluntary blood donors had circulating TTV DNA. Phylogenetic analysis revealed a predominance of genotype 1a. In India, TTV is transmitted mainly by nonparenteral routes and is not an important cause of chronic liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
3
7
3
Order By: Relevance
“…In the present study, TTV‐DNA was detected much more frequently, not only in AVH (80%) and FHF (76%) patients, but also in healthy blood donors (52%) when compared with those reported from other parts of the world, including India 2,11 , 12,17 . The present prevalence rate of TTV infection of 52% (26/50) in volunteer blood donors is similar to that reported from other developing countries such as Gambia and Brazil 18,19 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, TTV‐DNA was detected much more frequently, not only in AVH (80%) and FHF (76%) patients, but also in healthy blood donors (52%) when compared with those reported from other parts of the world, including India 2,11 , 12,17 . The present prevalence rate of TTV infection of 52% (26/50) in volunteer blood donors is similar to that reported from other developing countries such as Gambia and Brazil 18,19 .…”
Section: Discussionsupporting
confidence: 84%
“…Recent reports from Japan and other parts of the world show a prevalence rate of 52–92% among a healthy population 13,14,20 . These prevalence rates are much higher than those reported earlier from Japan and Western countries 2,11 , 12,17 …”
Section: Discussionmentioning
confidence: 91%
“…TTV genotype 1 was the predominant genotype in our study population, while few cases of genotype 2 were also reported. These results are in consonance with those of previous studies from India [41,42], including from our own center [36]. Our findings indicate that both assays were equally effective in detecting anti-TTV antibodies irrespective of the TTV genotype, possibly indicating a lack of genotype specificity of the antibodies detected.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, we found the prevalence of TTV among the healthy control subjects to be 28% using ORF1 specific primers, which is higher than the 7.4% prevalence reported by an earlier Indian study, 37 which used another set of ORF1 primers previously described by Simmonds et al 10 The discordance in the prevalence rates between the two studies may have been due to the variance in the choice of primers employed. It has been said that TTV viremia rates tend to increase with age and seem to peak in young adulthood.…”
Section: Percentage Of Positive Patients In a Category5contrasting
confidence: 69%
“…Earlier, this was also reported as the most prevalent strain in India. 37 Moreover, genotype 1 is the TTV genotype most frequently contended to have specific disease association. 7,[18][19][20]33 The role of the virus in liver pathology has been repeatedly deliberated.…”
Section: Percentage Of Positive Patients In a Category5mentioning
confidence: 99%